Exploring the Porosity in Ceramics at the nm Scale: From Understanding Historical Ceramics to Innovative Materials Design - Mondelli, Claudia (2020)
Ceramics are complex objects and a rich source of information: they constitute a large part of the staple memory of past and present human activities. A deep understanding of traditional ceramics is an essential key to designing new ceramic materials. The demanding synthesis of ceramics with fine-tuned properties, such as enhanced mechanical, electrical, optical or magnetic characteristics, must be associated with cutting-edge analysis procedures in order to improve the engineering process. In this context, we describe a neutron-based non-destructive approach to investigating the nanoporosity of an historical pottery matrix as an effective investigation technique for exploring both traditional and advanced ceramic materials.